Tantangan Guru Pendidikan Agama Islam dalam Menghadapi Siswa Generasi Z di Sekolah Menengah Kejuruan: Challenges of Islamic Education Teachers in Dealing with Generation Z Students at Vocational School - Naila Aisyal Ulum; Muhammad Hasyim (Madrasah Tsanawiyah DDI Cilellang, 2024)
Islamic Education (PAI) plays a strategic role in shaping students’ character and morals, especially amid technological advancement and globalization. However, PAI teachers face complex challenges in teaching Generation Z students who are digital natives, critical thinkers, independent learners, and prefer interactive learning. This study aims to analyze the challenges faced by PAI teachers and the innovative strategies applied in addressing Generation Z students at NU Sunan Ampel Vocational School, Poncokusumo. This quali¬ta-tive research employed observation, interviews, and documentation as data collection techniques and descriptive analysis as a data analysis technique. The findings reveal key challenges, including students’ low interest in conventional methods, exposure to radical and liberal religious content, limited technology integration, and students’ critical attitudes toward religious discourse. To address these challenges, teachers implemented innovative strategies such as interactive digital media, project-based learning, and integration of Islamic values in counseling. These strategies significantly improved students’ partici¬pation, comprehension, and application of religious values in daily life. The study recommends enhancing teachers’ digital competencies and school policy support to realize a more adaptive and relevant PAI learning model for Generation Z.